Evaluation of elite British cyclists: the role of the squad medical - Callaghan, M. J.; Jarvis, C. (British Journal of Sports Medicine, 1996)
OBJECTIVE: To describe and report results from the procedures and protocols used by the British Cycling Federation during the squad medicals of its elite cyclists. METHODS: Screening of over 500 elite riders has been done by doctors, dentists, physiotherapists, opticians, and dietitians since 1990. A questionnaire provided additional information on musculoskeletal problems. RESULTS: 523 riders have been examined and 92 (17.5%) have been referred for further assessment or treatment. Most of these riders were sent either to their own general practitioner or to the British Olympic Medical Centre. The questionnaire was completed by 81% of riders. Low back pain was the most common problem that riders encountered (60%), and knee pain the second most common (33%). Four riders failed the eye examination, and a further 11 were classed as borderline. Twenty one per cent of riders undergoing dental examination needed further dental treatment. CONCLUSIONS: The squad medical is an important and useful strategy for evaluating elite British cyclists. It shows that a structured system can help early diagnosis and treatment to provide injury-free cyclists at the start of a competitive season. The results from the questionnaire confirm previously unsubstantiated opinions about the incidence of musculoskeletal injuries in cyclists.